The Impact of Tax Policy on Small Business Development in Uzbekistan - Mamadaliyeva Marjona Shavkat qizi; Turayev Alijon Akmal o‘g‘li (Research Parks Publishers, 2026)
Small business and private entrepreneurship play a crucial role in ensuring sustainable economic growth, increasing employment, and improving regional economic stability in Uzbekistan. In recent years, the government of Uzbekistan has implemented large-scale tax reforms aimed at reducing the tax burden, simplifying tax administration, and supporting entrepreneurial activity. This study examines the impact of tax policy on the development of small businesses in Uzbekistan within the context of ongoing economic reforms. The main research objective is to evaluate how changes in tax policy influence small business activity, financial sustainability, investment behavior, and employment generation in Uzbekistan. The study applies a mixed-methods research design based on statistical analysis, comparative analysis, and qualitative policy assessment. Secondary data were collected from the State Tax Committee of Uzbekistan, the Statistics Agency under the President of the Republic of Uzbekistan, World Bank reports, and academic publications covering the period from 2018 to 2024.